1994
DOI: 10.1366/0003702944027309
|View full text |Cite
|
Sign up to set email alerts
|

Metastability in Monolayer Films Transferred onto Solid Substrates by the Langmuir-Blodgett Method: IR Evidence for Transfer-Induced Phase Transitions

Abstract: The rate at which a monomolecular film is deposited onto a solid substrate in the Langmuir-Blodgett process of preparing supported monolayer films influences the final structure of the transferred film. Attenuated total reflectance infrared spectroscopic studies of monolayers transferred to germanium substrates show that the speed at which the substrate is drawn through the air/water interface influences the final conformation in the hydrocarbon chains of amphiphilic film molecules. This transfer-induced effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…4a (not shown) shows less than 5% height values larger than 2.5 nm, which means that the repulsion effect of the mica on the negative phospholipid monolayer is low. The effect of the monolayer lifting due to substrate repulsion was not observed, demonstrating previous observations [36] for condensed phases. At this respect, it is necessary to bear in mind that monolayer transfer might affect the structure of the monolayer films.…”
Section: Atomic Force Measurementssupporting
confidence: 83%
See 2 more Smart Citations
“…4a (not shown) shows less than 5% height values larger than 2.5 nm, which means that the repulsion effect of the mica on the negative phospholipid monolayer is low. The effect of the monolayer lifting due to substrate repulsion was not observed, demonstrating previous observations [36] for condensed phases. At this respect, it is necessary to bear in mind that monolayer transfer might affect the structure of the monolayer films.…”
Section: Atomic Force Measurementssupporting
confidence: 83%
“…At this respect, it is necessary to bear in mind that monolayer transfer might affect the structure of the monolayer films. The transference can be effectively affected when it is performed at the gaseous and LE phases [36]. However, several authors have found that the transfer of the first lipidic monolayer is relatively easy at surface pressures above the LE state [33][34][35], even when the solid substrate and the monolayers may carry the same kind of electrical charge, probably because of the monolayer film greatly reduces the surface energy of the hydrated substrate in air [33].…”
Section: Atomic Force Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, due to diVerent adhesive interactions of the monolayer transferred to a solid substrate with respect to the monolayer Xoating on water, the mixing behaviour of Xoating and transferred monolayers is diVerent, leading to a possible substrate-mediated condensation of monolayers upon transfer (Spratte and Riegler, 1994). This eVect is however minimized when the Wlm molecules are transferred from condensed phases at high surface pressures (Rana et al, 1994). Furthermore, the recorded condensation into close-packed islands during transfer of fatty acids in the liquid expanded state is less pronounced at low pH (Sikes and Schwartz, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Studies of phospholipid films in dispersions, Langmuir layers, and Langmuir–Blodgett layers are well documented as biological membrane models 1. These assemblies have been studied by a wide range of techniques including NMR spectroscopy,2–14 X‐ray and electron diffraction,15–17 fluorescence spectroscopy,18–32 optical and spectroscopic microscopy,20, 22, 24, 33 scanning probe microscopies,34–37 and the vibrational spectroscopies FTIR,38–51 Raman,42, 52–63 and vibrational sum‐frequency generation 64–66. The vibrational spectroscopies provide much needed data about molecular structure and interactions between lipid molecules in such assemblies, particularly for the alkyl chain.…”
Section: Introductionmentioning
confidence: 99%